Characterization of HIV-1 CRF02_AG/A3/G unique recombinant forms identified among children in Larkana, Pakistan - Rashid, Abdur; Kang, Li; Yi, Feng; Mir, Fatima; Getaneh, Yimam; Shao, Yiming; Abidi, Syed Hani (Frontiers in Cellular and Infection Microbiology, 2023)
Co-circulation of different human immunodeficiency virus type 1 HIV-1 subtypes among infected populations can lead to the generation of new recombinants. In Pakistan, subtype A1 and CRF02_AG are the dominant strains circulating among key populations. The high prevalence of new HIV infections among the key populations highlights the possibility of recombination between the dominant strains, which can lead to the generation of new recombinants. Here, we identified a recombinant cluster composed of CRF02_AG, sub-subtype A3, and subtype G among HIV-infected children in Larkana. For the study, 10 retrospectively collected samples, with recombination signals in the pol gene, were used to perform a near full-length genome NFLG sequencing. Of the 10 samples, NFLG was successfully sequenced from seven samples. Phylogenetic analysis of the seven NFLGs showed that all recombinants formed a distinct monophyletic cluster and were distinct from known HIV-1 circulating recombinant forms CRFs. Recombination analyses showed that all seven NFLGs shared a similar recombinant structure consisting of CRF02_AG, sub-subtype A3, and subtype G, with a sub-subtype A3 fragment inserted into pol and vif regions spanning from (HXB2: 4218-5518), and a subtype G fragment inserted into vpu, rev, tat and env regions spanning from (HXB2: 5957-8250) of the CRF02_AG backbone. The identification of unique recombinant forms may indicate the presence and transmission of several co-circulating lineages in Larkana, giving rise to newer CRFs. This study also highlights the importance of continuous molecular surveillance to fully understand HIV-1 genetic diversity in Pakistan, particularly in Larkana, which is the epicenter of HIV outbreaks.